A TEACHER'S STRATEGIES IN EXPANDING DISCOURSE IN AN ENGLISH AS A FOREIGN LANGUAGE (EFL) CLASSROOM: A Case Study at a Primary School in Bandung Affiliated to an Islamic School in Singapore - Aisah, Eneng Elis (2011)
This study aims to uncover a teacher's strategies in expanding classroom discourse. The objectives include the investigation of types of the teacher's strategies, linguistic features of the expanded discourse and application of the principles of the expanded discourse in the classroom. This study is a descriptive-qualitative design in a school in Bandung affiliated to an Islamic School in Singapore. The participants were an English teacher and his nine students. The three audio recording data were analyzed by describing and comparing them to the theories and previous research on classroom discourse and discourse strategies particularly from Walsh (2002), Applebee et al. (2003), Nystard (2006), Mercer (2008), and Gibbons (2009). This research found that, firstly, the teacher adopted good rapport by using the students' name, the discourse marker 'please', and direct and indirect responses. The teacher uses referential question in the form of closed interrogative and open interrogative with question marker 'what' and 'who'. The teacher also provides more than two seconds of wait time after questioning and arguing. Moreover, the teacher uses uptake strategy in the form of open interrogative, closed interrogative and tag-questions. Secondly, it is discovered that the strategies adopted by the teacher have expanded the classroom discourse by the way the students elaborate, extend and enhance the information. The linguistic features of elaboration are the use of 'I mean' implicitly and the use of Indonesian language. The extension is signaled by the use of explicit conjunctions 'and', 'also', 'too' and implicit conjunction 'but'. The enhancement is featured by the use of explicit conjunctions 'because', 'so' and implicit 'therefore'. Thirdly, it is found that to some extent the use of the discourse strategies and the expansion system in the classroom by the teacher reflects the application of expanded classroom discourse principles, i.e. reflecting classroom as social interaction and developing the students' thinking. It is recommended that further research is to investigate the influence of teacher's strategies to the students' self esteem and curiosity as these two aspects seems important in encouraging the students to expand the discourse.